Keberadaan Konsep Mistis dalam Film Anak Jumbo Produksi Visinema - Wibowo, Eden Farelio; Yudono, Kristophorus Divinanto Adi (DIDAKTIS : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Jumbo has become the highest-grossing film in Indonesian history. Although it is packaged as a children's animated film, Jumbo contains elements of mysticism. This study aims to analyze and describe the existence of mysticism in the animated film Jumbo produced by Visinema. The research adopts a literary anthropology approach. The primary data source is the animated film Jumbo. Data were collected using a documentation technique, which involved carefully watching the film and taking detailed notes on indicators related to the presence of mysticism. Data validity was ensured through source and theoretical triangulation. The data analysis was conducted through the stages of data collection, reduction, presentation, and verification. Based on this process, the study found that Jumbo contains elements of mysticism, which manifest in material, spiritual, and moral forms. Each mystical element is evident in the film's scenes. This indicates that mystical content can be integrated into various creative genres, even those intended for children or that portray children's worlds.